HUBUNGAN ANEMIA PADA IBU HAMIL TRIMESTER I DENGAN KEJADIAN ABORTUS DI RUMAH SAKIT PELNI PETAMBURAN SELAMA PANDEMI TAHUN 2021 - Winsca Maghfirda Yasya (2023)
Abortion still be burden problem because of its impact on maternal morbidity and mortality. One of the leading causes of maternal death is bleeding due to complications caused by abortion. According to the WHO, the chances of abortion occurring are quite high. It is estimated that about 2-2.5% of miscarriages occur in Indonesia each year. Maternal death has three classic causes: hemorrhage, toxins, and infections. hemorrhage during pregnancy remains a major problem in Indonesia. This condition can cause problems for both mother and child. Mothers can die during pregnancy and as infancy. Therefore, research on anemia and abortion is needed. The purpose of this study is to clarify the relationship between anemia in early pregnancy and abortion frequency in Perni Petamburan Hospital in 2021. The sample for this study was an anemic patient who had an abortion at Perni Hospital in 2021. This study used an observational analysis design with a cohort study approach using medical records. about 40 respondent was randomize This study shown there is no significant association between anemia and abortion (p=0.442) among first trimester of pregnancy mother in 2021 Perni Petamburan Hospital.